Citizens’ Perceptions towards Transportation Tax and Retribution in Malang City, Indonesia - Dadang M Utomo; Astri Warih Anjarwi; Kartika Putri Kumalasari (TATALOKA, 2020)
This paper tries to look at the root cause of low ridership in public transport in the city of Malang, locally known as Angkutan Kota (Angkot), in a kind of non-traditional perspective. The decreasing interest of the people of Malang City towards the use of public transport was presumed partly due to the transportation tax and retribution policies that are somewhat not too restrictive. This study explains that 80% of people in Malang City consider the amount of Motor Vehicle Tax (PKB) is cheap and reasonable which is believed to drive people away from utilizing Angkot. On the other hand, surprisingly, parking fees for motorized vehicles for most people are considered quite burdensome. Thus, this study suggests that in addition to the need to improve the quality of public transport services, adjusting the amount of tax and the cost of parking for motorized vehicles in the city of Malang needs to be reconsidered to increase the interest of the people of Malang in using public transport.